Constructing organic-inorganic bimetallic hybrid materials based on the polyoxometalate backbone - Sharma, Kanika (Kansas State University, 2014)
The thesis focuses on the design and synthesis of novel organoimido delivery reagents capable of forming bimetallic polyoxometalate (POM) hybrids, and their use in the assembly of bimetallic hexamolybdate derivatives. These delivery reagents have been designed thoughtfully and separate organic moieties have been selected for coordinating to both the POM cluster and the second metal atom. A series of three ligands [4-aminopiperidine, 4-(4-aminophenyl) piperazine, and 4-(4-aminophenyl) piperidine] were selected and used to synthesize the dithiocarbamate metal-coordinating ligands, which in turn were used for preparing the corresponding metal (M = Cr, Mn, Fe, Co, Ni, Cu, Zn, Ag) complexes. All the complexes were characterized by infrared spectroscopy (IR). Reported routes were followed for the covalent grafting of these metal complexes onto hexamolybdate. But, the poor solubility of these metal complexes was found to be a major stumbling block in our endeavors to synthesize the dithiocarbamate based polyoxometalate hybrids. The observed poor solubility of metal dithiocarbamate complexes was overcome by synthesizing [potassium(I) tris(3,5-diphenylpyrazole)borate] and [potassium(I) tris(3,5-dimethylpyrazole)borate] via thermal dehydrogenative condensation between tetrahydroborate and the respective pyrazole molecule. A series of corresponding transition metal (M = Co, Ni, Cu, Mn) complexes of tris(3,5-diphenylpyrazole)borate and tris(3,5-dimethylpyrazole)borate were synthesized, and characterized by IR and UV-visible spectroscopy, and single crystal X-ray diffraction. The single crystal structure of [manganese(II) (tris(3,5-dimethylpyrazole)borate)2] turned out to an outlier as it displayed the formation of a bis-complex, thus having no substitutable anion for further reaction with dithiocarbamates. Thereafter, a series of metal dithiocarbamate complexes of these [hydrotris(pyrazolyl)borates] (M = Co, Ni, Cu ) were prepared using [sodium 4-aminopiperidyldithiocarbamate] and were characterized by IR and UV-visible spectroscopy. A remarkable improvement in the solubility of these metal dithiocarbamates in organic solvents was observed. Furthermore, attempts to covalently graft these complexes onto hexamolybdate cluster were undertaken, and found to be unsuccessful possibly due to the strong oxidizing nature of PPh[subscript]3Br[subscript]2 and hexamolybdate. Although, we were able to successfully tailor the solubility of the dithiocarbamate complexes to suit our needs, our efforts to achieve the primary goal of synthesizing dithiocarbamate based polyoxometalate hybrids have so far been unsuccessful. A series of three pyridyl based ligands i.e., 3,5-di(pyridin-2-yl)-4H-1,2,4-triazol-4-amine, 4-(pyridin-4-ylethynyl)aniline and 4-(pyridin-3-ylethynyl)aniline were synthesized and characterized. Covalent attachment of these ligands to hexamolybdate were attempted following various well-known routes. Although, no evidence of covalent attachment of 3,5-di(pyridin-2-yl)-4H-1,2,4-triazol-4-amine to hexamolybdate was observed, the covalent grafting of 4-(pyridin-4-ylethynyl)aniline and 4-(pyridin-3-ylethynyl)aniline to hexamolybdate cluster was successfully achieved. Characterization of these novel organic-inorganic hybrids was done using IR and NMR spectroscopy as analytical tools. Attempts have been undertaken to obtain single crystals of these hybrids. Also, a novel route involving halogen bonding as a purification and separation technique for pyridyl functionalized hexamolybdate hybrids is also being explored. The novel acetylacetonate moiety has been explored as an imidodelivery reagent for synthesizing hexamolybdate covalent hybrids, wherein [3-(4-((4-aminophenyl)ethynyl)phenyl)-4-hydroxypent-3-en-2-one] ligand has been successfully synthesized and characterized. Traditional methods along with unconventional methods such as heating at elevated temperatures and microwave reaction conditions, have so far proved to be unsuccessful in the synthesis of the hybrids. A series of the corresponding metal complexes have been synthesized and characterized, where the ligand and its corresponding copper(II) complex have been characterized by single crystal XRD. In the crystal structure of the copper complex, the metal ion sits in a slightly distorted square-planar pocket, where no coordination to the -NH[subscript]2 group is observed, which highlights the potential of using it as an imidodelivery reagent.
Keywords: Covalent Polyoxometalates Hybrids; Organometallic Chemistry; Chemistry (0485)